Co-Production in Urban Agriculture Programs in the Kosagrha Lestari Farmer Group, Medokan Ayu Village, Surabaya City - Fadhlan Firdaus Syafrudin; Susi Hardjati (Journal of Governance and Social Policy, 2025)
Agricultural land in this era is getting smaller, especially in urban areas. This happens because there has been a change in the function of agricultural land into settlements or industries. Therefore, one of the ways adopted by the Surabaya City Government to be able to meet food needs amid the increasingly narrow agricultural land, one of which is the Urban Farming Program. However, the agricultural program carried out in the Kosagrha Lestari farmer group still faces problems such as low community participation. Therefore, it is necessary to see how community participation in urban farming programs. The purpose of this research is to find out, describe and analyze how community participation in urban farming programs as a step to maintain food security in Surabaya City. This research used descriptive qualitative method. Data collection techniques used observation, interviews, and documentation. The results of research show that community participation in urban agriculture Kosagrha Lestari has been going well, although not all people are involved, especially in food security in Medokan Ayu Village.